Chimeric antigen receptor (CAR) T-cells in acute B-cell leukemia T-Zellen mit chimärem Antigenrezeptor (CAR) bei akuter B-Zell-Leukämie - Hudecek, M. (Best Practice Onkologie, 2019)
The clinical approval of gene-engineered CD19-specific (CD: cluster of differentiation) chimeric antigen receptor T-cells (CD19-CAR T-cells) for the treatment of acute lymphoblastic leukemia (ALL) has marked a new era of personalized cancer immunotherapy in Germany. The innovative mode-of-action is that antigen recognition by the CAR triggers the release of cytolytic granules and cytokines that lead to elimination of leukemic cells expressing the CD19 antigen. CAR T‑cells are a ‘living drug’ that can persist for months and potentially years in the patient’s body after a single infusion, thereby conferring leukemia eradication and also protection from relapse. CAR T-cell therapy will be available at specialized centers with experience in immunotherapy and has the potential to profoundly change and improve the treatment of hematologic malignancies.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Genetic therapy; Immunotherapy; adoptive; Neoplasms; Precursor cell lymphoblastic leukemia-lymphoma; Receptors; artificial